Zinner's syndrome: report of two cases and review of the literature. Issue 1 (December 2016) - Slaoui, Amine; Regragui, Souhail; Lasri, Abdelouahad; Karmouni, Tarik; El Khader, Khalid; Koutani, Abdellatif; Ibn Attya, Ahmed
Abstract Background Congenital malformations of the seminal vesicle are uncommon, and most of them are cystic malformations. If an insult occurs between the 4th and the 13 h gestational week, the embryogenesis of the kidney, ureter, seminal vesicle, and vas deferens could be altered. Cysts of the seminal vesicle may appear with a mass effect, dysuria, epididymitis, or obstruction of the gastrointestinal and genitourinary tracts. Approximately two thirds of them are associated with ipsilateral renal agenesis, because both the ureteral buds and seminal vesicles originate from the mesonephric (Wolffian) duct. They were first described by Zinner in 1914, and 200 cases of seminal vesicle cysts associated with ipsilateral renal agenesis have been reported in the literature. Most patients with this anomaly are asymptomatic until the third or fourth decade of life. Some cases have nonspecific symptoms such as prostatism, urinary urgency, dysuria, painful ejaculation, and perineal discomfort. Transrectal ultrasonography provides good visualization of the pelvic structures and allows guidance for aspiration of the cysts. Case presentation We present two cases of seminal vesicle cyst. The first patient had dysuria, increased frequency of urination, and haematuria. He was operated and benefited from a removal of the cyst with right ureterectomy and left ureteral reimplantation. The second patient had disorder of the digestive transit and he benefited from a laparoscopic removal of the cyst. Conclusions Seminal vesicle cysts combined with ipsilateral renal agenesis are rare urological anomalies. Usual symptoms that are caused by the seminal vesicle cysts are bladder irritation and obstruction as well as pain in the perineum and scrotum. Epididymitis is frequently found. Treatment consists to removing the seminal vesicle cyst.